Genetic analysis of sudden unexpected death cases: Evaluation of library preparation methods to handle heterogeneous sample material. (May 2021) - Scheiper-Welling, Stefanie; Körber, Stephanie; Geisen, Christof; Verhoff, Marcel A.; Kauferstein, Silke
Abstract: Over the past years, next-generation sequencing (NGS) technologies revolutionized the possibilities in a broad range of application areas. Also in the field of forensic genetics, NGS continuously gained in importance and attentiveness. A significant number of sudden cardiac deaths (SCD) in the young is due to heritable arrhythmia syndromes emphasizing the need of examining the genetic basis in these cases also with regard to the identification of relatives and/or patients being at risk. As a result, high-throughput methods became of increasing value in molecular autopsy investigations enabling the analysis of a broad spectrum of genes. Most standard protocols are optimized for high-quality samples and frequently not directly applicable to challenging forensic sample material. In the present study, we intended to examine a comprehensive gene panel associated with SCD and inherited arrhythmogenic disorders. We compared three different hybridization-based library preparation technologies in order to implement a suitable NGS workflow for heterogeneous, forensic as well as diagnostic sample material. The results obtained indicated, that the Illumina technologies Nextera DNA Flex and TruSeq were compatible with samples exhibiting varying levels of degradation. In comparison, the TruSight method also resulted in good sequencing data, but seemed to be more dependent on DNA integrity. The preparation protocols evaluated in our study are not restricted to molecular autopsy investigations and might be helpful for and transferrable to further forensic research applications. Highlights: 3 library preparation methods were tested for applicability with forensic samples. Adapted hybrid-capture protocols resulted in robust sequencing data analyzing SCDs. Illumina methods DNA prep and TruSeq were compatible with forensic sample material. High-quality data were obtained with samples showing varying levels of degradation. Hybrid-capture methods should be taken into account for postmortem genetic analyses.